Vulnérabilité des ptéridophytes au changement climatique et implications pour leur conservation au Togo (Afrique de l’Ouest) - Abotsi, K.E.; Kokou, K.; Rouhan, G.; Deblauwe, V. (Agentschap Plantentuin Meise, 2020)
Background and aims – The sustainable conservation of biodiversity requires a good understanding of the causes of its decline. Apart from human activities, climate change is the major threat to global biodiversity during the 21st century. Our study aims to determine the impact of climate change on pteridophytes in Togo.